All-solid-state flexible lithium ion battery with integrated structure and preparation method of all-solid-state flexible lithium ion battery
By using the thermal welding method to form an interfaceless composite layer structure in an all-solid-state lithium-ion battery, the problems of interface instability and poor flexibility are solved, and high conductivity and strong flexibility are achieved.
Patent Information
- Application Number
- CN202510206493.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-03-25
AI Technical Summary
Existing all-solid-state lithium-ion batteries have problems such as unstable interface, large interface impedance, and poor negative electrode flexibility, which affect energy storage performance and deformation capabilities.
The composite positive electrode layer, composite electrolyte layer and composite negative electrode layer are superimposed by thermal welding method to form an integrated structure without interfaces, and polymer electrolyte and inorganic solid electrolyte are used to improve conductivity and flexibility.
It realizes an integrated structure with high electron/ion conductivity and strong flexibility, reduces interface impedance, improves energy storage performance and cycling stability, and meets the bending and folding requirements of flexible batteries.
Smart Images

Figure CN119695296A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid-state lithium-ion battery preparation, and in particular relates to an all-solid-state flexible lithium-ion battery with an integrated structure and a preparation method thereof. Background Art
[0002] In recent years, the demand for rechargeable energy storage devices has increased significantly, and the requirements have also increased significantly. This is particularly evident in electric vehicles, mobile / wearable smart devices, and energy storage systems. Among various energy storage devices, lithium-ion batteries have been widely used in most portable electronic devices, such as smartphones and laptops, due to their high energy and high power density. However, traditional lithium-ion batteries use flammable liquid electrolytes with limited electrochemical windows, which leads to safety risks and difficulty in further improving energy density.
[0003] In contrast, all-solid-state batteries using solid electrolytes have attracted much attention due to their higher safety, electrochemical stability and high energy density. However, the interface instability caused by the redox reaction between the solid electrolyte and the electrode and the large interface impedance caused by the solid-solid rigid contact will affect the energy storage performance of the all-solid-state battery, such as rate, cycle stability, and capacity.
[0004] In this regard, the patent with publication number CN111129602A discloses a method for preparing an integrated solid-state battery, in which a solid electrolyte slurry is coated on an electrode layer to obtain an integrated structure to obtain better interface compatibility and improve the energy density and power density of the solid-state battery. The patent with publication number CN116705989A discloses a flexible polymer electrolyte silicon integrated electrode and its preparation method and application. By constructing a flexible polymer electrolyte / silicon integrated electrode, the interface contact resistance is greatly reduced, thereby achieving improved battery performance.
[0005] Although the above integrated structure of electrode / solid electrolyte can effectively solve the problem of large internal resistance of solid-state batteries, the following problems still exist: (1) Due to the porosity and pore size inside the electrode, the surface tension of the electrolyte solution, and the polarity of the electrolyte and electrode materials, the immersion depth of the electrolyte solution is limited, generally around a dozen to several dozen μm. If the electrode is too thin, the energy density of the solid-state battery will be reduced. (2) Although the polymer electrolyte fills the pores inside the electrode, the wettability of the polymer electrolyte on the electrode is enhanced, improving its ion transport pathway, but due to the introduction of too much insulating phase inside the electrode, the electronic conductivity will decrease. (3) The current integrated structure is mostly positive electrode / electrolyte integration, and the negative electrode uses metallic lithium. However, the metallic lithium of the negative electrode has poor flexibility and cannot meet the bending, folding and other deformation requirements required by flexible all-solid-state batteries.
[0006] In this regard, exploring an electrode / solid electrolyte with an integrated structure that has high electronic / ionic conductivity and strong flexibility to further improve the energy storage performance of solid-state batteries has become an urgent problem to be solved in this field. Summary of the invention
[0007] The present invention aims to solve one of the technical problems existing in the related art at least to a certain extent.
[0008] One object of the present invention is to provide an all-solid-state flexible lithium-ion battery with an integrated structure, in which the electrode layer and the electrolyte layer are combined into an integrated structure, thereby effectively avoiding the problems of poor contact between key material layers and poor compatibility caused by separate stacked assembly batteries.
[0009] Another object of the present invention is to provide a method for preparing the above-mentioned all-solid-state flexible lithium-ion battery with an integrated structure.
[0010] In order to achieve the above-mentioned objectives, the present invention provides, on the one hand, an all-solid-state flexible lithium-ion battery with an integrated structure, comprising: a composite positive electrode layer, a composite electrolyte layer and a composite negative electrode layer stacked in sequence, wherein the composite positive electrode layer, the composite electrolyte layer and the composite negative electrode layer are thermally melted to adjacent layers without interfaces, thereby forming an integrated state.
[0011] A further preferred technical solution of the present invention is that the composite positive electrode layer and the composite negative electrode layer are thin films obtained by a doctor blade coating method of active material, conductive agent and polymer electrolyte; the thickness is 30-100 μm; The composite positive electrode layer and the composite negative electrode layer each contain at least 20% to 40% of a polymer electrolyte and 10% to 15% of a conductive agent; The composite electrolyte layer is a thin film obtained by a blade coating method of a polymer electrolyte, and has a thickness of 30-50 μm.
[0012] Preferably, the composite positive electrode layer, the composite negative electrode layer and the composite electrolyte layer are prepared by using the same polymer electrolyte; the polymer electrolyte comprises a polymer, an inorganic solid electrolyte and a lithium salt; Wherein, the polymer is one of polyvinylidene fluoride, polyethylene oxide, polyvinyl alcohol, polyacrylonitrile, polymethyl methacrylate or polypropylene oxide; The inorganic solid electrolyte is one of a perovskite type, a NASICON type, a LISICON type or a garnet type solid electrolyte; Lithium salt is LiClO 4 、LiPF 6 、LiAsF 4 or LiBF 4 One of; The proportion of polymer in polymer electrolyte is 60%~90%, the proportion of inorganic solid electrolyte in polymer electrolyte is 5%~20%, and the proportion of lithium salt in polymer electrolyte is 5%~20%.
[0013] Preferably, the conductive agent includes graphene, carbon nanotubes and carbon black; Among them, graphene accounts for 20%~30% of the conductive agent, carbon nanotubes account for 30%~40% of the conductive agent, and carbon black accounts for 30%~50% of the conductive agent.
[0014] Preferably, the active material of the composite positive electrode layer is one of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide or nickel cobalt lithium manganese oxide; The active material of the composite negative electrode layer is one of lithium titanate, soft carbon, hard carbon or graphite.
[0015] Preferably, the composite positive electrode layer and the composite negative electrode layer are both self-supporting structures without the metal current collector.
[0016] Preferably, the electronic conductivity of the composite positive electrode layer and the composite negative electrode layer is 1×10 -6 ~5×10 -5 S / cm, and the ionic conductivity is 5×10 -5 ~5×10 -4 S / cm.
[0017] Another aspect of the present invention provides a method for preparing an all-solid-state flexible lithium-ion battery with an integrated structure, comprising the following steps: S1. The positive electrode active material, the conductive agent and the polymer electrolyte are mixed in proportion, then added into NMP solvent, stirred for 2 hours, ball-milled for 8 hours, cast on a glass plate, placed in a blast drying oven to remove the solvent, and after drying, the film is peeled off from the glass plate to obtain a composite positive electrode layer; S2, the negative electrode active material, the conductive agent and the polymer electrolyte are mixed in proportion, then added to the NMP solvent, stirred for 2 hours, ball-milled for 8 hours, cast on a glass plate, placed in a blast drying oven to remove the solvent, and after drying, the film is peeled off the glass plate to obtain a composite positive electrode layer; S3, the polymer, inorganic filler and lithium salt are mixed in proportion, then added to NMP solvent, stirred at 65°C-85°C for 5h, then intermittently ultrasonicated at 40°C for 30min, finally transferred to a cell crusher for 10min, the viscous slurry is evenly coated on a polytetrafluoroethylene plate, placed in a vacuum drying oven to remove the solvent, and after drying, the film is peeled off the polytetrafluoroethylene plate to obtain a composite electrolyte layer; S4, stacking the composite positive electrode layer, the composite electrolyte layer, and the composite negative electrode layer in sequence, adjusting the parameters of the hot roller press, and using the hot roller press to heat-weld the composite positive electrode layer / composite electrolyte layer / composite negative electrode layer together so that there is no interface between the three, thereby obtaining an integrated flexible composite layer; S5. In an argon glove box, the prepared integrated flexible combination layer is encapsulated with an aluminum-plastic film to obtain the all-solid-state flexible lithium-ion battery.
[0018] Furthermore, in step S4, when the composite positive electrode layer / composite electrolyte layer / composite negative electrode layer are thermally welded together using a hot roller press, the hot roller press is performed 3 to 10 times, the roller spacing is gradually reduced by 5 microns, the hot roller pressing temperature is 80 to 110° C., and the roller speed is 5 to 20 rpm.
[0019] Furthermore, before hot rolling, the composite positive electrode layer, the composite electrolyte layer and the composite negative electrode layer are first heated to a temperature range sufficient for plastic deformation; then, the composite positive electrode layer, the composite electrolyte layer and the composite negative electrode layer are plastically deformed using the rolling pressure of the hot rolling machine.
[0020] Beneficial effects: (1) The present invention realizes the interface-free integration of the composite electrode layer and the composite electrolyte layer through hot rolling, which can effectively avoid the problems of poor contact and poor compatibility between key material layers caused by separate stacked assembly batteries. At the same time, the composite electrode and the composite electrolyte use the same polymer material, which is beneficial to improve the interfacial adhesion between the composite electrode and the composite electrolyte, while reducing the interface impedance and providing a continuous lithium ion transmission path from the electrolyte / electrode interface to the interior of the electrode, so that the all-solid-state battery has excellent cycle stability.
[0021] (2) In the composite electrode, the polymer electrolyte filled between the active materials allows ions to be transported through the composite electrolyte, and the three-dimensional conductive network constructed by graphene, carbon nanotubes, and carbon black provides an electron transport pathway. This ion / electron dual transport channel can improve the ionic conductivity and electronic conductivity of the composite electrode, thereby enabling the composite electrode to have excellent energy storage performance under higher loading conditions; and hot pressing of multi-layer thin electrodes into dense thick electrodes can also effectively improve their energy density.
[0022] (3) Polymer electrolytes have the advantages of low cost, high flexibility, and easy to form a close interface with electrodes. A certain proportion of polymer electrolytes is added to the composite electrode, eliminating the need for a metal current collector. This can prevent external stress from damaging the composite electrode structure, while at the same time withstanding the volume changes of active materials during the battery charge and discharge cycle, and has excellent flexibility and bendability. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1It is a schematic structural diagram of the all-solid-state flexible lithium-ion battery with an integrated structure of the present invention.
[0024] Figure 2 This is a cross-sectional scanning electron microscope photograph of the integrated flexible composite layer of Example 1.
[0025] Figure 3 This is a charge and discharge curve diagram of the all-solid-state flexible lithium-ion battery with an integrated structure prepared in Example 1.
[0026] Figure 4 This is the specific capacity change curve of the all-solid-state flexible lithium-ion battery with an integrated structure prepared in Example 1 under different folding times. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings in the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments, and they should not be understood as limitations on the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. In the description of the present invention, it should be understood that the terms used are only for descriptive purposes and cannot be understood as indicating or implying relative importance.
[0028] The experimental methods and test methods in the following examples without specifying specific conditions are selected according to conventional methods in the art. Batteries of the same specifications are used for testing and comparison in each example.
[0029] Unless otherwise specified, the chemical reagents and solvents in the present invention are all commercially available analytically pure or chemically pure reagents. Conductive carbon black was purchased from Kruder Chemical Technology Co., Ltd.; carbon nanotube slurry (NMP solvent) was purchased from Kruder Chemical Technology Co., Ltd., with a solid content of 5%; pure graphene oily NMP conductive slurry was purchased from Suzhou Carbon Graphene Technology, with a solid content of 5%.
[0030] Combine the following Figure 1-Figure 4 The present invention describes an all-solid-state flexible lithium-ion battery with an integrated structure and a preparation method thereof.
[0031] Embodiment 1: This embodiment provides an all-solid-state flexible lithium-ion battery with an integrated structure, comprising: a composite positive electrode layer, a composite electrolyte layer and a composite negative electrode layer stacked in sequence, wherein the composite positive electrode layer, the composite electrolyte layer and the composite negative electrode layer are thermally welded to form an integrated state without an interface between adjacent layers. Both the composite positive electrode layer and the composite negative electrode layer are self-supporting structures, and the metal current collector is removed.
[0032] The specific preparation method of the all-solid-state flexible lithium-ion battery with an integrated structure comprises the following steps: (1) Preparation of composite positive electrode layer: Lithium iron phosphate (LiFePO 4 ), polymer electrolyte, and conductive agent are added to 10g N,N-dimethylpyrrolidone (NMP) in a mass ratio of 6:2.5:1.5 in sequence and stirred for 2h, and then put into a ball mill for 8h, and then filtered through a sieve to obtain a fully mixed and uniform slurry. The scraper scale is controlled to coat it on a polytetrafluoroethylene plate, and it is placed in a vacuum oven with a set temperature of 120°C and dried for 24h to remove the solvent. After the drying step is completed, the film is peeled off from the polytetrafluoroethylene plate to obtain a composite positive electrode layer with a thickness of 40um.
[0033] The polymer electrolyte is composed of polyvinylidene fluoride (PVDF), inorganic electrolyte LLZTO, and lithium salt (LiTFSI) in a mass ratio of 6:1:3. The conductive agent is composed of carbon black (Super-P), graphene, and carbon nanotubes in a mass ratio of 1:0.5:1.5.
[0034] (2) Preparation of composite negative electrode layer: Lithium titanate (Li 4 Ti 5 O 12 ), polymer electrolyte, and conductive agent are added to 10g N,N-dimethylpyrrolidone (NMP) in a mass ratio of 6:2.5:1.5 in sequence and stirred for 2h, then put into a ball mill and milled for 8h, filtered through a sieve to obtain a fully mixed and uniform slurry, and coated on a polytetrafluoroethylene plate by controlling the scraper scale, and placed in a vacuum oven with a set temperature of 120°C and dried for 24h to remove the solvent. After the drying step is completed, the electrode layer is peeled off from the polytetrafluoroethylene plate to obtain a composite negative electrode layer with a thickness of 40um.
[0035] The polymer electrolyte is composed of polyvinylidene fluoride (PVDF), inorganic electrolyte LLZTO, and lithium salt (LiTFSI) in a mass ratio of 6:1:3. The conductive agent is composed of carbon black (Super-P), graphene, and carbon nanotubes in a mass ratio of 1:0.5:1.5.
[0036] (3) Preparation of composite electrolyte layer: polyvinylidene fluoride (PVDF), inorganic electrolyte LLZTO, and lithium salt (LiTFSI) were added to a certain amount of N,N-dimethylformamide (DMF) in a mass ratio of 6:1:3 and stirred for 2 h. The mixture was then placed in a ball mill and milled for 8 h. The mixture was filtered through a molecular sieve to obtain a uniform viscous slurry. The slurry was coated on a polytetrafluoroethylene plate by controlling the scale of a scraper. The slurry was placed in a vacuum oven at a set temperature of 120 °C and dried for 24 h to remove the solvent. After the drying step was completed, the electrolyte layer was peeled off the polytetrafluoroethylene plate to obtain a composite electrolyte layer with a thickness of 20 μm.
[0037] (4) Preparation of an integrated flexible composite layer: The obtained composite positive electrode layer, composite electrolyte layer and composite negative electrode layer are stacked in sequence. Before hot rolling, the composite positive electrode layer, composite electrolyte layer and composite negative electrode layer are first heated to a temperature range sufficient for plastic deformation. Then, the temperature of the hot rolling machine is set to 80°C, the roller speed is 5 rpm, and the roller spacing is 95 μm. The rolling is repeated 5 times, with the roller spacing being reduced by 5 μm each time, to obtain an integrated all-solid-state battery cell.
[0038] (5) Assembly, preparation and testing of all-solid-state flexible lithium-ion batteries: (a) In a glove box filled with argon, the composite positive electrode of the all-solid-state flexible lithium-ion battery is bonded to the aluminum tab, the composite negative electrode is bonded to the nickel tab, and the battery is sealed with an aluminum-plastic film. The battery is then evacuated and hot-pressed at 80°C for 1 min to obtain an all-solid-state flexible lithium-ion battery with a soft-pack integrated structure. No electrolyte or separator is required between the layers. (b) Test battery cycle performance with a voltage range of 1V-2.5V, a current density of 0.2C and a test temperature of 25°C.
[0039] The electronic conductivity of the prepared composite positive electrode was 5.1×10 -4 S cm -1 , the ionic conductivity is 3.9×10 -6 S cm -1 The all-solid-state flexible lithium-ion battery with an integrated structure has a specific capacity of 158 mAh g at 0.2C. -1 , the specific capacity is 106 mAh g at 2C -1 ; After 1000 cycles at 0.2C, the capacity retention rate is 89.9%; after folding 10 times, the capacity retention rate is 99.9%.
[0040] Figure 1 It shows that in the composite electrode layer, the polymer electrolyte filled between the active materials provides a lithium ion transport pathway, and the electronic conduction network embedded in the polymer electrolyte provides an electron transport pathway.
[0041] Figure 2 The results show that the hot rolling technology forms a dense interface between the composite electrode layer and the composite electrolyte layer, with no pores and no obvious stratification. Good interface contact is conducive to reducing the interface impedance between the composite electrolyte and the composite electrode. At the same time, the significant improvement of the wettability of the composite electrode and the composite electrolyte interface can effectively promote the transmission of Li+, induce uniform deposition of metallic lithium, and inhibit the growth of lithium dendrites.
[0042] Figure 3 It shows that after 1000 charge and discharge cycles at a current density of 0.1C, its initial capacity is 158 mAh g-1 and 142mAh g -1 , with good cycle stability.
[0043] Figure 4 It shows that after folding 10 times, the specific capacity changes very little and the retention rate is 99.9%, indicating that the structure designed by the present invention has excellent flexibility.
[0044] Example 2: This example provides an all-solid-state flexible lithium-ion battery with an integrated structure, the general structure of which is the same as that of Example 1, except for the difference in preparation materials and film thickness.
[0045] The specific preparation method of the all-solid-state flexible lithium-ion battery with an integrated structure comprises the following steps: (1) Preparation of composite positive electrode layer: Lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O 2 ), polymer electrolyte, and conductive agent were sequentially added into N,N-dimethylpyrrolidone (NMP) in a mass ratio of 5:3:2 and mixed, and then a composite positive electrode layer with a thickness of 40 μm was prepared according to the method of step (1) of Example 1.
[0046] (2) Preparation of composite negative electrode layer: Graphite, polymer electrolyte and conductive agent were sequentially added into N,N-dimethylpyrrolidone (NMP) at a mass ratio of 5:3:2 and mixed, and then a composite negative electrode layer with a thickness of 30 μm was prepared according to the method of step (2) of Example 1.
[0047] (3) Preparation of composite electrolyte layer: Polyvinyl alcohol (PVA), inorganic electrolyte TiO 2 、Lithium salt (LiClO 4 ) was added to a certain amount of N,N-dimethylformamide (DMF) in a mass ratio of 6:1:3 and mixed, and then a composite electrolyte layer with a thickness of 20 μm was prepared according to the method of step (3) of Example 1.
[0048] (4) Preparation of an integrated flexible composite layer: The obtained composite positive electrode layer, composite electrolyte layer and composite negative electrode layer are stacked in sequence, and the temperature of the hot roller press is set to 80°C, the roller speed is 5 rpm, and the roller spacing is 85 μm. The rolling is repeated 5 times, and the roller spacing is reduced by 5 μm each time to obtain an integrated all-solid-state battery cell.
[0049] (5) Assembly, preparation and testing of all-solid-state batteries: The assembly, preparation and testing of the all-solid-state battery of Example 2 are the same as those of Example 1, except that the voltage range is changed to 2.8V-4.2V.
[0050] The electronic conductivity of the prepared composite positive electrode was 4.38×10 -4 S cm -1 , the ionic conductivity is 1.96×10 -6 S cm -1 The all-solid-state flexible lithium-ion battery with an integrated structure has a specific capacity of 175 mAh g at 0.2C. -1 , the specific capacity at 2C is 120.8 mAh g -1 ; After 1000 cycles at 0.2C, the capacity retention rate was 88.6%; after folding 10 times, the capacity retention rate was 99.8%.
[0051] Example 3: This example provides an all-solid-state flexible lithium-ion battery with an integrated structure, the general structure of which is the same as that of Example 1, except for the difference in preparation materials and film thickness.
[0052] The specific preparation method of the all-solid-state flexible lithium-ion battery with an integrated structure comprises the following steps: (1) Preparation of composite positive electrode layer: Lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O 2 ), polymer electrolyte, and conductive agent were sequentially added into N,N-dimethylpyrrolidone (NMP) in a mass ratio of 6:2.5:1.5 and mixed, and then a composite positive electrode layer with a thickness of 40 μm was prepared according to the method of step (1) of Example 1.
[0053] (2) Preparation of composite negative electrode layer: Graphite, polymer electrolyte and conductive agent were sequentially added into N,N-dimethylpyrrolidone (NMP) at a mass ratio of 6:2.5:1.5 and mixed, and then a composite negative electrode layer with a thickness of 30 μm was prepared according to the method of step (2) of Example 1.
[0054] (3) Preparation of composite electrolyte layer: Polyvinylidene fluoride (PVDF), inorganic electrolyte LLZTO, and lithium salt (LiTFSI) were added to a certain amount of N,N-dimethylformamide (DMF) in a mass ratio of 6:1:3 and mixed. Then, a composite electrolyte layer with a thickness of 20 μm was prepared according to the method of step (3) of Example 1.
[0055] (4) Preparation of an integrated flexible composite layer: The obtained composite positive electrode layer, composite electrolyte layer and composite negative electrode layer are stacked in sequence, and the temperature of the hot roller press is set to 110°C, the roller speed is 8 rpm, and the roller spacing is 85 μm. The rolling is repeated 5 times, and the roller spacing is gradually reduced by 5 μm to obtain an integrated all-solid-state battery cell.
[0056] (5) Assembly, preparation and testing of all-solid-state batteries: The assembly, preparation and testing of the all-solid-state battery of Example 3 are the same as those of Example 1, except that the voltage range is changed to 2.8V-4.2V.
[0057] The electronic conductivity of the prepared composite positive electrode was 3.85×10 -4 S cm -1 , the ionic conductivity is 2.76×10 -6 S cm -1 The all-solid-state flexible lithium-ion battery with an integrated structure has a specific capacity of 172 mAh g at 0.2C. -1 , the specific capacity at 2C is 115.6 mAh g -1 ; After 1000 cycles at 0.2C, the capacity retention rate is 90.4%; after folding 10 times, the capacity retention rate is 99.6%.
[0058] Example 4: This example provides an all-solid-state flexible lithium-ion battery with an integrated structure, the general structure of which is the same as that of Example 1, except for the difference in preparation materials and film thickness.
[0059] The specific preparation method of the all-solid-state flexible lithium-ion battery with an integrated structure comprises the following steps: (1) Preparation of composite positive electrode layer: Lithium iron phosphate (LiFePO 4 ), polymer electrolyte, and conductive agent were sequentially added into N,N-dimethylpyrrolidone (NMP) in a mass ratio of 5:3:2 and mixed, and then a composite positive electrode layer with a thickness of 40 μm was prepared according to the method of step (1) of Example 1.
[0060] (2) Preparation of composite negative electrode layer: Lithium titanate (Li 4 Ti 5 O 12 ), polymer electrolyte, and conductive agent were sequentially added into N,N-dimethylpyrrolidone (NMP) in a mass ratio of 5:3:2 and mixed, and then a composite negative electrode layer with a thickness of 40 μm was prepared according to the method of step (2) of Example 1.
[0061] (3) Preparation of composite electrolyte layer: Polyvinyl alcohol (PVA), inorganic electrolyte TiO 2 、Lithium salt (LiClO 4 ) was added to a certain amount of N,N-dimethylformamide (DMF) in a mass ratio of 6:1:3 and mixed, and then a composite electrolyte layer with a thickness of 20 μm was prepared according to the method of step (3) of Example 1.
[0062] (4) Preparation of an integrated flexible composite layer: The obtained composite positive electrode layer, composite electrolyte layer and composite negative electrode layer are stacked in sequence, and the temperature of the hot roller press is set to 110°C, the roller speed is 8 rpm, and the roller spacing is 95 μm. The rolling is repeated 5 times, and the roller spacing is gradually reduced by 5 μm to obtain an integrated all-solid-state battery cell.
[0063] (5) Assembly, preparation and testing of all-solid-state batteries: The assembly, preparation and testing of the all-solid-state battery of Example 4 are the same as those of Example 1.
[0064] The electronic conductivity of the prepared composite positive electrode was 4.96×10 -4 S cm -1 , the ionic conductivity is 3.88×10 -6 S cm -1 The all-solid-state flexible lithium-ion battery with an integrated structure has a specific capacity of 157 mAh g at 0.2C. -1 , the specific capacity at 2C is 102.8 mAh g -1 ; After 1000 cycles at 0.2C, the capacity retention rate was 87.4%; after folding 10 times, the capacity retention rate was 99.2%.
[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. An all-solid-state flexible lithium-ion battery with an integrated structure, characterized in that: include: The composite positive electrode layer, composite electrolyte layer and composite negative electrode layer are stacked in sequence, and the composite positive electrode layer, composite electrolyte layer and composite negative electrode layer are thermally fused to form an integrated state without interfaces between adjacent layers.
2. The all-solid-state flexible lithium-ion battery with an integrated structure according to claim 1, characterized in that: The composite positive electrode layer and the composite negative electrode layer are thin films obtained by a doctor blade coating method of active material, conductive agent and polymer electrolyte; the thickness is 30-100 μm; The composite positive electrode layer and the composite negative electrode layer each contain at least 20% to 40% of a polymer electrolyte and 10% to 15% of a conductive agent; The composite electrolyte layer is a thin film obtained by a blade coating method of a polymer electrolyte, and has a thickness of 30-50 μm.
3. The all-solid-state flexible lithium-ion battery with an integrated structure according to claim 2, characterized in that: The composite positive electrode layer, the composite negative electrode layer and the composite electrolyte layer are prepared by using the same polymer electrolyte; the polymer electrolyte comprises a polymer, an inorganic solid electrolyte and a lithium salt; Wherein, the polymer is one of polyvinylidene fluoride, polyethylene oxide, polyvinyl alcohol, polyacrylonitrile, polymethyl methacrylate or polypropylene oxide; The inorganic solid electrolyte is one of a perovskite type, a NASICON type, a LISICON type or a garnet type solid electrolyte; The lithium salt is one of LiClO4, LiPF6, LiAsF4 or LiBF4; The proportion of polymer in polymer electrolyte is 60%~90%, the proportion of inorganic solid electrolyte in polymer electrolyte is 5%~20%, and the proportion of lithium salt in polymer electrolyte is 5%~20%.
4. The all-solid-state flexible lithium-ion battery with an integrated structure according to claim 2, characterized in that: The conductive agent includes graphene, carbon nanotubes and carbon black; Among them, graphene accounts for 20%~30% of the conductive agent, carbon nanotubes account for 30%~40% of the conductive agent, and carbon black accounts for 30%~50% of the conductive agent.
5. The all-solid-state flexible lithium-ion battery with an integrated structure according to claim 2, characterized in that: The active material of the composite positive electrode layer is one of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide or nickel cobalt lithium manganese oxide; The active material of the composite negative electrode layer is one of lithium titanate, soft carbon, hard carbon or graphite.
6. The all-solid-state flexible lithium-ion battery with an integrated structure according to claim 1, characterized in that: The composite positive electrode layer and the composite negative electrode layer are both self-supporting structures without the metal current collector.
7. The all-solid-state flexible lithium-ion battery with an integrated structure according to claim 1, characterized in that: The electronic conductivity of the composite positive electrode layer and the composite negative electrode layer is 1×10 -6 ~5×10 -5 S / cm, and the ionic conductivity is 5×10 -5 ~5×10 -4 S / cm.
8. A method for preparing an all-solid-state flexible lithium-ion battery with an integrated structure, characterized in that: The steps include: S1. The positive electrode active material, the conductive agent and the polymer electrolyte are mixed in proportion, then added into NMP solvent, stirred for 2 hours, ball-milled for 8 hours, cast on a glass plate, placed in a blast drying oven to remove the solvent, and after drying, the film is peeled off from the glass plate to obtain a composite positive electrode layer; S2, the negative electrode active material, the conductive agent and the polymer electrolyte are mixed in proportion, then added to the NMP solvent, stirred for 2 hours, ball-milled for 8 hours, cast on a glass plate, placed in a blast drying oven to remove the solvent, and after drying, the film is peeled off the glass plate to obtain a composite positive electrode layer; S3, the polymer, inorganic filler and lithium salt are mixed in proportion, then added to NMP solvent, stirred at 65°C-85°C for 5h, then intermittently ultrasonicated at 40°C for 30min, finally transferred to a cell crusher for 10min, the viscous slurry is evenly coated on a polytetrafluoroethylene plate, placed in a vacuum drying oven to remove the solvent, and after drying, the film is peeled off the polytetrafluoroethylene plate to obtain a composite electrolyte layer; S4, stacking the composite positive electrode layer, the composite electrolyte layer, and the composite negative electrode layer in sequence, adjusting the parameters of the hot roller press, and using the hot roller press to heat-weld the composite positive electrode layer / composite electrolyte layer / composite negative electrode layer together so that there is no interface between the three, thereby obtaining an integrated flexible composite layer; S5. In an argon glove box, the prepared integrated flexible combination layer is encapsulated with an aluminum-plastic film to obtain the all-solid-state flexible lithium-ion battery.
9. The preparation method according to claim 8, characterized in that: In step S4, when the composite positive electrode layer / composite electrolyte layer / composite negative electrode layer are thermally melted together using a hot roller press, the hot roller press is performed 3 to 10 times, the roller spacing is gradually reduced by 5 microns, the hot roller pressing temperature is 80 to 110° C., and the roller speed is 5 to 20 rpm.
10. The preparation method according to claim 8, characterized in that: In step S4, before hot rolling, the composite positive electrode layer, the composite electrolyte layer and the composite negative electrode layer are first heated to a temperature range sufficient for plastic deformation; then, the composite positive electrode layer, the composite electrolyte layer and the composite negative electrode layer are plastically deformed using the rolling pressure of the hot rolling machine.
Citation Information
Patent Citations
Preparation method of integrally formed solid-state battery
CN111129602A
Flexible polymer electrolyte silicon integrated electrode and preparation method and application thereof
CN116705989A
Solid-state battery and manufacturing method thereof
CN112349956A
Preparation method of current collector-free electrode and application of current collector-free electrode in supercapacitor
CN113725013A
Integrated all-solid-state battery based on ceramic-based electrolyte sheet and preparation method of integrated all-solid-state battery
CN114759269A